Additive Fertigung - Gausemeier, Jürgen; Schmidt, Michael; Anderl, Reiner; Schmid, Hans-Joachim; Leyens, Christoph; Seliger, Günther; Karg, Michael; Kage, Martin

Geschäftsmodelle für Industrie 4.0 - Digitalisierung als große Chance für zukünftigen Unternehmenserfolg - Echterhoff, Benedikt; Gausemeier, Jürgen; Koldewey, Christian; Mittag, Tobias; Schneider, Marcel; Seif, Heiko (Digital vernetzt. Transformation der Wertschöpfung.: Szenarien, Optionen und Erfolgsmodelle für smarte Geschäftsmodelle, Produkte und Services)

Management des geistigen Eigentums im Rahmen der strategischen Produktplanung - Eckelt, Daniel; Gausemeier, Jürgen; Gronemeyer, Christoph Uwe (12. Symposium für Vorausschau und Technologieplanung 8. und 9. Dezember 2016)

Strategische Release-Planung als Ansatz zur systematischen Produktwertsteigerung - Kühn, Arno; Dumitrescu, Roman; Gausemeier, Jürgen (Vorausschau und Technologieplanung, 12. Symposium für Vorausschau und Technologieplanung, 8. und 9. Dezember 2016)

Integration Additiver Produktionstechnologien in den Produktentstehungsprozess - Brandis, Rinje; Lessmann, Christoph; Schneider, Marcel; Wanzek, Anna-Lena (Vorausschau und Technologieplanung, Symposium für Vorausschau und Technologieplanung, Band 360)

Integration additiver Fertigungstechnologien in die Produktentstehung - Brandis, Rinje; Wanzek, Anna-Lena; Schneider, Marcel; Gausemeier, Jürgen (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb 111(11))

Anwendung von Methoden der Produktentstehung auf Basis des Systemmodells mechatronischer Systeme - Greinert, Matthias; Tschirner, Christian; Holtmann, Jörg (Tag des Systems Engineering 2016)
Das Systemmodell ist der Kern des Model-Based Systems Engineering (MBSE). Während jedoch im Systems Engineering dem Zusammenspiel von Produkt und Projekt ein hoher Stellenwert beigemessen wird, liegt der Fokus im MBSE noch sehr stark auf technischen Prozessen. Im Hinblick auf die Idee des Systemmodells als zentrale Datenquelle sollten auch Stakeholder jenseits der direkten Entwicklungsaktivitäten das Systemmodell entsprechend nutzen können und davon profitieren. Dazu wird ein Demonstrator vorgestellt, welcher die Anwendung einer Komplexitätsanalyse auf Basis des Systemmodells mechatronischer Systeme stellvertretend für Methoden in Sinne der technischen Managementprozesse der ISO/IEC 15288 aufzeigt. Grundlage des Demonstrators bildet das Systemmodell eines Pedelecs. Die darin modellierten Strukturen dienen als Input für die Komplexitätsanalyse. Über die automatisierte Anwendung der Komplexitätsanalyse ergibt sich als Output ein Portfolio, das die Komplexität der funktionserfüllenden Komponenten mit der Bewertung der Funktionalität in Beziehung setzt und somit eine Beurteilung und entsprechende Handlungsempfehlungen der Komponenten ermöglicht.

Interactive VR-based Visualization for Material Flow Simulations - Berssenbrügge, Jan; Stöcklein, Jörg; Köchling, Daniel (Virtual, Augmented and Mixed Reality VAMR 2016 Held as Part of HCI International 2016, LNCS 9740)

Detecting White Spots in Innovation-Driven Intellectual Property Management - Eckelt, Daniel; Dülme, Christian; Gausemeier, Jürgen; Hemel, Simon (Technology Innovation Management Review 6(7))

Value Network Design for Innovations: Developing Alternative Value Network Drafts - Kage, Martin; Drewel, Marvin; Gausemeier, Jürgen; Schneider, Marcel (Technology Innovation Management Review 6(7))

Maschinen und Anlagen auf dem Weg zu Cyber-Physical Systems - Westermann, Thorsten; Iwanek, Peter; Dumitrescu, Roman (19. IFF-Wissenschaftstage: Kooperation im Anlagenbau)

Systematic Business Model Implementation - From Concepts to Real Business - Echterhoff, Benedikt; Gausemeier, Jürgen; Hirschter, Tobias (Proceedings of the 27th ISPIM Innovation Conference, 19. - 22. Jun. 2016 International Society for Professional Innovation Management (ISPIM))
Nowadays business model innovation has become a task, every company has to face in order to stay competitive. Even though, good business concepts are created every day, only few of them make their way from paper to real business. This is mostly due to barriers during implementation: How do we validate our business model? How do we derive requirements and measures? In which way can we keep internal resistance to a minimum? Even though the literature on business model innovation is extensive, business model implementation is covered seldomly. The paper at hand presents a methodology for systematic business model implementation. Key components are a maturity model for business concept validation, an impact analysis for the identification of requirements as well as master plan of action which serves as a communication strategy.

Future-oriented consolidation of product portfolios – Create space for innovations - Dülme, Christian; Eckelt, Daniel; Friebe, Milena; Gausemeier, Jürgen (Proceedings of the 27th ISPIM Innovation Conference, 19. - 22. Jun. 2016 International Society for Professional Innovation Management (ISPIM))

Perspective on the design of a decision support system based on Linked Data for process planning - Rehage, Gerald; Joppen, Robert; Gausemeier, Jürgen (Procedia Technology)

Intelligent Production System Planning with Virtual Design Reviews - Köchling, Daniel; Berssenbrügge, Jan; Schluessler, Joel; Stöcklein, Jörg (Proceedings of 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering (SysInt) 2016, Band 26)

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Journal of Computing and Information Science in Engineering, Band 16(3))

Advanced Traffic Simulation Framework for Networked Driving Simulators - Abdelgawad, Kareem; Henning, Sven; Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (AAC2016 (IFAC), 8th IFAC Symposium on Advances in Automotive Control (AAC 2016))

Modeling Language for Value Networks - Schneider, Marcel; Mittag, Tobias; Gausemeier, Jürgen (25th International Association for Management of Technology Conference Proceedings, 25th International Association for Management of Technology Conference, Band 25)

Business Model Based Configuration of Value Creation Networks - Mittag, Tobias; Schneider, Marcel; Gausemeier, Jürgen (25th International Association for Management of Technology Conference Proceedings, Band 25)

Industrie 4.0 - Internationaler Benchmark, Zukunftsoptionen und Handlungsempfehlungen für die Produktionsforschung - Gausemeier, Jürgen; Klocke, Fritz; Dülme, Christian; Eckelt, Daniel; Kabasci, Patrick; Kohlhuber, Martina; Schön, Nico; Schröder, Stephan; Wellensiek, Markus

DESIGN OF A SELF-OPTIMISING PRODUCTION CONTROL SYSTEM - Köchling, Daniel; Gausemeier, Jürgen; Joppen, Robert; Mittag, Tobias (14th International DESIGN Conference)

Integrated and iterative systems engineering and software requirements engineering for technical systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Journal of Software Evolution and Process)
The development of software-intensive technical systems involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and a system model. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline-specific development to start, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived in previous work a systematic transition from MBSE to model-based software requirements engineering. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. In this paper, we extend this approach with support for subsequent process iterations and provide an algorithm for the automated steps. We illustrate the approach and perform a case study with an example of an automotive embedded system.

Strategische Produktplanung - Adaptierbare Methoden, Prozesse und IT-Werkzeuge für die Planung der Marktleistungen von morgen - Gausemeier, Jürgen; Ovtcharova, Jivka; Amshoff, Benjamin; Eckelt, Daniel; Elstermann, Matthes; Placzek, Markus; Wiederkehr, Olga

Value Network Design for Innovations - Kage, Martin; Drewel, Marvin; Gausemeier, Jürgen; Schneider, Marcel (Proceedings of the 5th ISPIM Innovation Forum)

Die sich selbst optimierende Lackieranlage - Iwanek, Peter; Kühn, Arno (Journal für Oberflächentechnik 3(56))

Detecting white spots in innovation-driven intellectual property management - Eckelt, Daniel; Dülme, Christian; Gausemeier, Jürgen; Hemel, Simon (International Society for Professional Innovation Management (ISPIM))

Musik - Edition – Medien: Detmolder Projekte Der Digitalen Musikwissenschaft - Richts, Kristina; Röwenstrunk, Daniel

Systematik zur innovationsorientierten Kompetenzplanung - Rübbelke, René

Intelligente Arbeitsvorbereitung in der Cloud - Rehage, Gerald; Isenberg, Florian; Reisch, Raphael-Elias; Weber, Jens; Jurke, Benjamin; Pruschek, Peter (wt Werkstattstechnik online (1/2-2016))
Auf dem Weg zu Industrie 4.0 wird die Arbeitsvorbereitung zunehmend von kognitiver Informationstechnik unterstützt. Der Beitrag präsentiert die bisherigen Ergebnisse des Forschungsprojekts „Intelligente Arbeitsvorbereitung auf Basis virtueller Werkzeugmaschinen“. Projektziel ist eine Cloud-Dienstleistungsplattform zur Reduzierung der Rüst- und Nebenzeiten durch eine intelligente Planung. Hierzu zählen unter anderem die Auswahl und Validierung alternativer Maschinen sowie die automatische Optimierung der Einrichtungsparameter durch verteilte Simulationen.

Instrumentarium für einen lösungsmusterbasierten Entwurf fortgeschrittener mechatronischer Systeme - Anacker, Harald

Systematik zur technologie-induzierten Produkt- und Technologieplanung - Wall, Marina

Systematik zur lösungsmusterbasierten Entwicklung von Frugal Innovations - Lehner, Anne-Christin

Methodik zur Bewertung von Produktionssystemen in der frühen Entwicklungsphase - Rudtsch, Vinzent

Ernährung und psychische Erkrankungen - Libuda, Lars; Antel, J.; Hebebrand, J.; Föcker, M. (Der Nervenarzt)

Strategische Produkt- und Prozessplanung - Gausemeier, Jürgen; Echterfeld, Julian; Amshoff, Benjamin (Handbuch Produktentwicklung)

Systematik zur musterbasierten Entwicklung technologie-induzierter Geschäftsmodelle - Amshoff, Benjamin

Außerschulische Nutzung neuer Technologien durch Jugendliche und der Zusammenhang mit dem Erwerb computer- und informationsbezogener Kompetenzen - Vennemann, Mario; Eickelmann, Birgit; Drossel, Kerstin; Bos, Wilfried (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Gelingensbedingungen IT-bezogener Lehrerkooperation als Merkmal von Schulqualität - Drossel, Kerstin; Schulz-Zander, Renate; Lorenz, Ramona; Eickelmann, Birgit (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Vertiefende Analysen zu ICILS 2013 – Befunde und mögliche Entwicklungsperspektiven - Eickelmann, Birgit; Gerick, Julia; Drossel, Kerstin; Bos, Wilfried (ICILS 2013. Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

ICILS 2013. Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen

Der Sozialindex: Theoretische Fundierung und forschungspraktische Relevanz für die Erfassung der Schülerkomposition von Gymnasien - Becker, Dominik; Drossel, Kerstin; Schwanenberg, Jasmin; Wendt, Heike; Bos, Wilfried (Sozialindices für Schulen. Hintergründe, Methoden und Anwendung)

Alterung spritzgegossener thermoplastischer Mikrobauteile - Meister, Steve

Einfluss der Nanopartikelgeometrie auf ie Buchzähigkeit und das Ermüdungsrissausbreitungsverhalten von Epoxidharzen - Kothmann , Martin H.

Rheologische und verarbeitungstechnische Eigenscahften von reaktiv prozessierten Polethelnterephthalaten - Härth , Michael

Der Einfluss stoffschlüssiger Fügeverfahren auf die Verbundfestigkeit flammgeschützter Kunststoffe - Evers , Fabian

Berechnung und Simulation von Feststoffförderprozesse in Einschneckenextrudern bis in den Hochgeschwindigkeitsbereich - Leßmann , Sebastian

Prozessphasenoptimierte Simulation und Modellierung des Spritzgießsonderverfahrens GITBlow - Seidel, Stefan

Entwicklung und Validierung konstruktiver Merkmale bei thermoplastischen Kunststoffblindverschraubungen mit dichtendem Hinterschnitt - Krugmann , Jens

Verarbeitung von PET auf gleichläufigen Doppelschneckenextrudern - Herken , Tobias

Ein Beitrag zur Veränderung der Kunststoffoberfläche durch Atmosphärendruck-Plasma - Leister , Christian

Relevance of Morning and Evening Energy and Macronutrient Intake during Childhood for Body Composition in Early Adolescence - Diederichs, Tanja; Roßbach, Sarah; Herder, Christian; Alexy, Ute; Buyken, Anette (Nutrients)

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts, Universität Leipzig, 7. bis 12. März 2016)
Welche Informationen über Unternehmenszusammenschlüsse werden in Zeitungsnachrichten vermittelt, und wie können diese Informationen automatisch extrahiert werden? Dies soll am Beispiel des Verhaltens von Aktionären während eines Zusammenschlusses ermittelt werden. Dazu werden die wichtigsten Aussagen über das Votum der Aktionäre im Hinblick auf eine automatische Erkennung sprachlich analysiert. Im Fokus stehen dabei die Berichte über Aktionärsabstimmungen hinsichtlich der Annahme bzw. Ablehnung eines Übernahmeangebots.

Webmonitoring - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Webmonitoring

Sentimentanalyse - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Sentimentanalyse

Text Mining - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Text Mining

Crawler (fokussiert / nicht fokussiert) - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Crawler

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

Congestion Games with Mixed Objectives - Leder, Lennart

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai-Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

On-chip generation of photon-triplet states - Krapick, Stephan; Brecht, Benjamin; Herrmann, Harald; Quiring, Viktor; Silberhorn, Christine (Optics Express)

The FiESTA data model: a novel approach to the representation of heterogeneous multimodal interaction data - Menke, Peter

Competition of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen (Theoretical Economics Letters)
On an intermediate goods market with asymmetric production technologies as well as vertical and horizontal product differentiation we analyze the influence of simultaneous competition for resources and customers. The intermediaries face either price or quantity competition on the output market and a monopolistic, strategically acting supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Moreover, the well-known welfare advantage of price competition can in general be no longer confirmed in our model with an endogenous input market and asymmetric intermediaries.

Competition in Markets with Intermediaries - Manegold, Jochen

Comparison of different Definitions of Chosen-Ciphertext Security in Encryption schemes - Porzenheim, Laurens

Geodaten in Social Media als Informationsquelle in Krisensituationen - Mirbabaie, Milad; Tschampel, N.; Stieglitz, Stefan (Proceedings of the 9th Multikonferenz Wirtschaftsinformatik)

Volunteered Geographic Information and its Implications for Disaster Management - Mirbabaie, Milad; Stieglitz, Stefan; Volkeri, S. (Proceedings of the 49th Hawaii International Conference on System Sciences)

Commitment Schemes - Definitions, Variants, and Security - Bemmann, Kai Sören

Experimentelle und numerische Untersuchungen des Crashverhaltens hybridgefügter Verbindungen - Hein, David; Meschut, Gerson; Matzenmiller, Anton; Nelson, Alexander (16. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Werkstoffgerechte Fügetechnologien als Schlüssel für innovative Mischbauweisen - Hein, David; Meschut, Gerson (Anwendertreff Leichtbau)

Churn- and DoS-resistant Overlay Networks Based on Network Reconfiguration - Drees, Maximilian; Gmyr, Robert; Scheideler, Christian (Proceedings of the 28th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We present three robust overlay networks: First, we present a network that organizes the nodes into an expander and is resistant to even massive adversarial churn. Second, we develop a network based on the hypercube that maintains connectivity under adversarial DoS-attacks. For the DoS-attacks we use the notion of a Omega(log log n)-late adversary which only has access to topological information that is at least Omega(log log n) rounds old. Finally, we develop a network that combines both churn- and DoS-resistance. The networks gain their robustness through constant network reconfiguration, i.e., the topology of the networks changes constantly. Our reconguration algorithms are based on node sampling primitives for expanders and hypercubes that allow each node to sample a logarithmic number of nodes uniformly at random in O(log log n) communication rounds. These primitives are specific to overlay networks and their optimal runtime represents an exponential improvement over known techniques. Our results have a wide range of applications, for example in the area of scalable and robust peer-to-peer systems.

Erweichungszonen beim Widerstandspunktschweißen von DP- und CP-Stählen – Analyse und Bewertung der Verbindungen im Hinblick auf die Tragfähigkeit

Challenge Accepted! - The Impcat of Goal Achievement on Subsequent User Effort and Implications of a Goal's Difficulty - von Rechenberg, Tobias; Gutt, Dominik (Proceedings of the 24th Conference on Information Systems (ECIS), Istanbul)
We empirically investigate the impact of successful goal achievement on future effort to attain the next goal in a recurring goal framework. We use data from a popular German Question & Answer community where goals are represented in the form of badges. In particular, our analysis of this data hinges on the fact, that in this Question & Answer community, badges in a hierarchical badge system are in-creasingly challenging to attain up to a certain badge. After this certain badge, the difficulty level sud-denly drops and remains constant throughout up to the last badge in the hierarchy. Our findings indi-cate that after successful badge achievement users increase their subsequent effort to attain the next badge, but only as long as badges represent a challenge to the user. According to our analysis, we identify self-learning to be the key driver of this behavior.

Imprecise Matching of Requirements Specifications for Software Services Using Fuzzy Logic - Platenius, Marie C.; Shaker, Ammar; Becker, Matthias; Hullermeier, Eyke; Schäfer, Wilhelm (IEEE Transactions on Software Engineering)

Ontologie-Erstellung mittels Text-Mining aus App-Marktplätzen am Beispiel des Google Marketplace - Heck, Eduard

Innovationsmanagement an Hochschulen: Maßnahmen zur Unterstützung der Digitalisierung von Studium und Lehre - Budde, Jannica; Oevel, Gudrun (INFORMATIK 2016)

Der Ton macht die Musik. Digitalisierung von Forschungsprozessen nicht nur in der Musikwissenschaft - Oevel, Gudrun ("Ei, dem alten Herrn zoll' ich Achtung gern'". Festschrift für Joachim Veit zum 60. Geburtstag)

G´schichten aus dem Rechnerwald: Sieben auf einen Streich - Oevel, Gudrun (Kooperation von Rechenzentren. Festkolloquium für Gerhard Schneider zum 60. Geburtstag)

Ontologie-basierte Extraktion funktionaler Softwareanforderungen am Fallbeispiel mobiler Kommunikationsapplikationen - Schwentker, Christoph

On-The-Fly Construction of Provably Correct Service Compositions - Templates and Proofs - Walther, Sven; Wehrheim, Heike (Science of Computer Programming)
Today, service compositions often need to be assembled or changed on-the-fly, which leaves only little time for quality assurance. Moreover, quality assurance is complicated by service providers only giving information on their services in terms of domain specific concepts with only limited semantic meaning.In this paper, we propose a method for constructing service compositions based on pre-verified templates. Templates, given as workflow descriptions, are typed over a (domain-independent) template ontology defining concepts and predicates. Their meaning is defined by an abstract semantics, leaving the specific meaning of ontology concepts open, however, only up to given ontology rules. Templates are proven correct using a Hoare-style proof calculus, extended by a specific rule for service calls. Construction of service compositions amounts to instantiation of templates with domain-specific services. Correctness of an instantiation can then simply be checked by verifying that the domain ontology (a) adheres to the rules of the template ontology, and (b) fulfills the constraints of the employed template.

On- and Off-Topic Classification and Semantic Annotation of User-Generated Software Requirements - Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing (EMNLP))
Users prefer natural language software requirements because of their usability and accessibility. When they describe their wishes for software development, they often provide off-topic information. We therefore present an automated approach for identifying and semantically annotating the on-topic parts of the given descriptions. It is designed to support requirement engineers in the requirement elicitation process on detecting and analyzing requirements in user-generated content. Since no lexical resources with domain-specific information about requirements are available, we created a corpus of requirements written in controlled language by instructed users and uncontrolled language by uninstructed users. We annotated these requirements regarding predicate-argument structures, conditions, priorities, motivations and semantic roles and used this information to train classifiers for information extraction purposes. The approach achieves an accuracy of 92% for the on- and off-topic classification task and an F1-measure of 72% for the semantic annotation.

The Game of Reciprocation Habits - Polevoy, Gleb; de Weerdt, M.M.; Jonker, C.M. (Proceedings of the 2016 European Conference on Artificial Intelligence)
Keywords: agents; action; repeated reciprocation; fixed; floating; network; Nash equilibrium; social welfare; price of anarchy; price of stability; convex combination

The Convergence of Reciprocation - Polevoy, Gleb; de Weerdt, Mathijs; Jonker, Catholijn (Proceedings of the 2016 International Conference on Autonomous Agents and Multiagent Systems)
Keywords: agent's influence; behavior; convergence; perron-frobenius; reciprocal interaction; repeated reciprocation

On the Parameterized Parallel Complexity and the Vertex Cover Problem - Abu-Khzam, Faisal N.; Li, Shouwei; Markarian, Christine; Meyer auf der Heide, Friedhelm; Podlipyan, Pavel (Proceedings of the 10th International Conference on Combinatorial Optimization and Applications (COCOA))
Efficiently parallelizable parameterized problems have been classified as being either in the class FPP (fixed-parameter parallelizable) or the class PNC (parameterized analog of NC), which contains FPP as a subclass. In this paper, we propose a more restrictive class of parallelizable parameterized problems called fixed-parameter parallel-tractable (FPPT). For a problem to be in FPPT, it should possess an efficient parallel algorithm not only from a theoretical standpoint but in practice as well. The primary distinction between FPPT and FPP is the parallel processor utilization, which is bounded by a polynomial function in the case of FPPT. We initiate the study of FPPT with the well-known k-vertex cover problem. In particular, we present a parallel algorithm that outperforms the best known parallel algorithm for this problem: using O(m) instead of O(n2) parallel processors, the running time improves from 4logn+O(kk) to O(k⋅log3n), where m is the number of edges, n is the number of vertices of the input graph, and k is an upper bound of the size of the sought vertex cover. We also note that a few P-complete problems fall into FPPT including the monotone circuit value problem (MCV) when the underlying graphs are bounded by a constant Euler genus.

Eigenkapitalverzehr und Substanzbesteuerung deutscher Unternehmen durch eine Vermögensteuer – eine empirische Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Stichprobe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen, deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300 % der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; Ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

40 issues of ICAME News/ICAME Journal - Mindt, Ilka (ICAME Journal 40)

An interview with Joybrato Mukherjee, the Chair oft he ICAME Board - Kytö, Merja; Stenström, Anna-Brita; Mindt, Ilka (ICAME Journal 40)

Tax Loss Offset Restrictions and Biased Perceptions of Risky Investments - Mehrmann, Annika; Sureth-Sloane, Caren

The diachronic development of 'COME TO V' - Mindt, Ilka (Silesian Studies in English 2015)

On the Design and Defense of Networks - An Experimental Investigation - Endres, Angelika Elfriede

On the abuse of market power - an economic perspective of Microsoft antitrust cases - Pehlivan, Muhammet

Introduction to the Special Issue on SPAA 2014 (Transactions on Parallel Computing (TOPC))

Das Eisenacher Regulativ und das Wiesbadener Programm. Die Diskussion um den evangelischen Kirchenbau und die Wiesbadener Kirchenbauten des 19. Jahrhunderts - Seng, Eva- Maria (Das Wiesbadener Programm und seine Bedeutung für den Kirchenbau. Zum Gedächtnis an Prof. Dr. Gottfried Kiesow)

Palmanova, eine Idealstadt im Friaul - Seng, Eva- Maria (ZIBALDONE. Zeitschrift für italienische Kultur der Gegenwart, No. 60, Herbst 2015)

Patrimoine culturel immatériel: plaidoyer pour une vision globale du patrimione culturel - Seng, Eva- Maria (Mutations de la culture patrimoniale)

Aus Fehlern lernen? Was kann man bei der Vergabe des Titels immaterielles Kulturerbe aus den Erfahrungen mit dem materiellen Kulturerbe ableiten und verbessern? - Seng, Eva- Maria (Altes Zeug: Beiträge zur Diskussion zum nachhaltigen Kulturgutschutz)

Confidentiality and Authenticity for Distributed Version Control Systems - A Mercurial Extension - Lass, Michael; Leibenger, Dominik; Sorge, Christoph (Proc. 41st Conference on Local Computer Networks (LCN))
Version Control Systems (VCS) are a valuable tool for software development and document management. Both client/server and distributed (Peer-to-Peer) models exist, with the latter (e.g., Git and Mercurial) becoming increasingly popular. Their distributed nature introduces complications, especially concerning security: it is hard to control the dissemination of contents stored in distributed VCS as they rely on replication of complete repositories to any involved user. We overcome this issue by designing and implementing a concept for cryptography-enforced access control which is transparent to the user. Use of field-tested schemes (end-to-end encryption, digital signatures) allows for strong security, while adoption of convergent encryption and content-defined chunking retains storage efficiency. The concept is seamlessly integrated into Mercurial---respecting its distributed storage concept---to ensure practical usability and compatibility to existing deployments.
Keywords: access control; distributed version control systems; mercurial; peer-to-peer; convergent encryption; confidentiality; authenticity

Imprecise Matching of Requirements Specifications for Software Services using Fuzzy Logic - Platenius, Marie Christin; Shaker, Ammar; Becker, Matthias; Hüllermeier, Eyke; Schäfer, Wilhelm (IEEE Transactions on Software Engineering (TSE), presented at ICSE 2017)
Today, software components are provided by global markets in the form of services. In order to optimally satisfy service requesters and service providers, adequate techniques for automatic service matching are needed. However, a requester’s requirements may be vague and the information available about a provided service may be incomplete. As a consequence, fuzziness is induced into the matching procedure. The contribution of this paper is the development of a systematic matching procedure that leverages concepts and techniques from fuzzy logic and possibility theory based on our formal distinction between different sources and types of fuzziness in the context of service matching. In contrast to existing methods, our approach is able to deal with imprecision and incompleteness in service specifications and to inform users about the extent of induced fuzziness in order to improve the user’s decision-making. We demonstrate our approach on the example of specifications for service reputation based on ratings given by previous users. Our evaluation based on real service ratings shows the utility and applicability of our approach.

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo

Das Politische und die Politik im Vormärz